PERLINDUNGAN HUKUM JUAL BELI HAK ATAS TANAH SECARA LISAN (STUDI PUTUSAN NOMOR: 114/PDT/2015/PT.MDN) - AMIR MAHMUD BRUTU (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Budiman Ginting, SH, MHum2.  Dr. Jelly Leviza, SH, MHum3.  Dr. Maria Kaban, SH, MHum Every transfer of land title through a sale and purchase has to be made before a PPAT (Land Title Registrar). A sale and purchase is a mutual agreement in which a seller promises to hand over his ownership rights over something, and a buyer promises to pay for the price consisting of an amount of money as a reward from the ownership right acquisition. The objective of the research is to discover the position of the land title that is verbally acquired pursuant to the positive law in Indonesia, to study the legal protection for the verbal sale and purchase of land title when the seller defaults, and to analyze the juridical and non-juridical consideration of the judge in the ruling No.114/PDT/2015/PT.MDN. This is an analytical descriptive research with normative juridical approach. Qualitative analysis method is employed to process and analyze the Court Ruling and the prevailing laws and regulations.Keywords: Sale and Purchase, Land Title, Verbal, Default